Challenges in reading English academic texts for non-English major students of an Indonesian university - Dardjito, Hanandyo; Rolls, Nicola; Setiawan, Ari; Sumekto, Didik Rinan (Studies in English Language and Education, 2023)
This study examines the barriers to reading academic texts among university students for whom English is a foreign language. While many previous studies have focused on instructional design for building academic reading skills, this study focuses on the fundamental issues that need consideration before setting up the instructional design for English academic reading. Taking an interpretive phenomenological viewpoint, this study applied a qualitative method through an online survey and interviews. Due to the Covid-19 pandemic, online data collection was the most accessible means of approaching the students. Ninety-five students from various non-English study programs (courses) at a private university voluntarily responded to the open-ended online questionnaire, providing survey data. Five students provided further data through individual interviews on their academic reading challenges. A thematic analysis of the survey data revealed four themes and eight subthemes representing the students challenges, which were explored further in the interviews. These challenges and the relationships among them are discussed. The results suggest that most students depended on single-word meanings as their prime strategy for achieving comprehension. However, this strategy also represented the most notable challenge in their effective reading of English academic texts. They failed to comprehend the text effectively because their translation did not make sense. Furthermore, the nature of the reading strategies of the student cohort had an impact on their baseline reading proficiency.